(untitled) (Research, Society and Development, 2022)
Research on insect colonization points to anthropic impacts as determining the structuring of this community. The present study aims to analyze the colonization process of Chironomidae in streams with different degrees of anthropic impacts. Nine similar streams in the municipality of Poços de Caldas (MG) were commercialized 12 traps, consisting of polyethylene bottles. The codes were classified according to their environmental protection in Natural Preserved (PN) and Urban Impacted (IU). 100g of Typha domingensis was placed in each bottle as substrate. Every fortnight, three bottles were removed from each stream, making a total period of 60 days. In the laboratory, the material was sorted and the Chironomidae larvae were mounted on slides for identification to the genus level. Then, after removing the biological variables, a Non-Metric Multidimensional Scaling (NMDS) analysis was performed using a Bray-Curtis dissimilarity matrix. Correspondence was noted between the abiotic variables measured from each environment with the groups found in the Chironomidae family. This relationship between the genera and the genera found showed that urbanization causes changes in the groups of these insects, growing bioindicators, such as an increase in larvae and an increase in the number of genera.